Selection of active plant extracts against the coffee leaf miner Leucoptera coffeella (Lepidoptera: Lyonetiidae) - D.S. Alves; D.F. Oliveira; G.A. Carvalho; D.A Carvalho; L.P. Souza; O. Lasmar (Universidade Estadual Paulista, 2013)
Aiming to contribute to the development of alternative control methods of the coffee leaf miner, Leucoptera coffeella (Guérin-Mèneville & Perrottet, 1842) (Lepidoptera: Lyonetiidae), a search for plants able to produce active substances against this insect was carried out, with species collected during different periods of time in the Alto Rio Grande region, (Lavras, Minas Gerais, Brazil). Coffee leaves containing L. coffeella mines were joined with 106 extracts from 77 plant species and, after 48 hours, the dead and alive caterpillars were counted. The extracts from Achillea millefolium, Citrus limon, Glechoma hederacea, Malva sylvestris, Mangifera indica, Mentha spicata, Mirabilis jalapa, Musa sapientum, Ocimum basiculum, Petiveria alliaceae, Porophyllum ruderale, Psidium guajava, Rosmarinus officinalis, Roupala montana, Sambucus nigra and Tropaeolum majus showed the highest mortality rates.